Bu’s theorem in the positive situation - Bougoutaia Amar; Belacel Amar (Moroccan Journal of Pure and Applied Analysis, 2022)
In this paper, we valorize the relationship between positive p−summing operators and positive strongly q−summing operators using (Contemp. Math. 328, 145 − 149 (2003)).